2023
DOI: 10.3389/fonc.2023.1226939
|View full text |Cite
|
Sign up to set email alerts
|

TTCC-2019-02: real-world evidence of first-line cetuximab plus paclitaxel in recurrent or metastatic squamous cell carcinoma of the head and neck

Jordi Rubió-Casadevall,
Beatriz Cirauqui Cirauqui,
Javier Martinez Trufero
et al.

Abstract: ObjectivesThe aim of this study was to confirm the efficacy of the ERBITAX scheme (paclitaxel 80 mg/m2 weekly and cetuximab 400 mg/m2 loading dose, and then 250 mg/m2 weekly) as first-line treatment for patients with recurrent/metastatic squamous cell carcinoma of the head and neck (SCCHN) who are medically unfit for cisplatin-based (PT) chemotherapy.Materials and methodsThis retrospective, non-interventional study involved 16 centers in Spain. Inclusion criteria were to have started receiving ERBITAX regimen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Accordingly, taxane-based chemotherapy might be more feasible to combine with moleculartargeted therapy than platinum-based anticancer drug in SGC. In patients with head and neck SCC, Cmab-PTX was well-tolerated even in patients with poor general conditions [42]. Because only 1 patient suffered from grade 4 AE despite 85.7% of patients were older than 70 years in this study, Cmab-PTX would be an effective and tolerable regimen to treat SGC.…”
Section: Characteristics Of Patients and Treatment Outcomesmentioning
confidence: 76%
“…Accordingly, taxane-based chemotherapy might be more feasible to combine with moleculartargeted therapy than platinum-based anticancer drug in SGC. In patients with head and neck SCC, Cmab-PTX was well-tolerated even in patients with poor general conditions [42]. Because only 1 patient suffered from grade 4 AE despite 85.7% of patients were older than 70 years in this study, Cmab-PTX would be an effective and tolerable regimen to treat SGC.…”
Section: Characteristics Of Patients and Treatment Outcomesmentioning
confidence: 76%
“…This study compared gold nanoparticles with titanium nanoparticles but did not add molecularly targeted drugs, such as cetuximab, which was performed in the current study. In other reports, cetuximab and trastuzumab were used to direct AuNPs toward cancer to enhance the effects of radiotherapy [22][23][24][25][26][27]. Chattopadhyay et al reported that HER2-targeted AuNPs increased the antitumor effect of radiotherapy in a xenograft model of breast cancer and that AuNPs are not harmful to normal tissue in vitro and in vivo [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…The addition of AuNPs in this study increased the antitumor effects of radiotherapy and cetuximab, but the combination did not completely eliminate tumors in vivo. Cetuximab has been clinically applied in combination with taxane-based anticancer agents, such as paclitaxel, in the treatment of difficult-to-resect tumors [26]. Hallal et al reported that the fixed-dose combination of gold nanoparticles and cetuximab itself was cytotoxic for rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce severe adverse effects and increase the reactivity of cetuximab, it has been combined with gold nanoparticles and radiotherapy procedures. Gold nanoparticles increased the efficiency of cetuximab, but complete eradication of tumors in vivo was not observed [121].…”
Section: Optimization Of Transmucosal Controlled Failure Systems In O...mentioning
confidence: 99%